Evaluation of the Relationship between Baseline Autonomic Tone and Haemodynamic Effects of Dexmedetomidine - Magdalena Wujtewicz; Paweł Twardowski; Tomasz Jasiński; Katarzyna Michalska-Małecka; Radosław Owczuk (MDPI AG, 2023)
Dexmedetomidine, a central α-2 agonist, is used for procedural sedation and for conscious sedation influences on heart rate and blood pressure. Authors verified whether it is possible to predict bradycardia and hypotension with the use of heart rate variability (HRV) analysis for an autonomic nervous system (ANS) activity assessment. The study included adult patients of both sexes with an ASA score of I or II scheduled for ophthalmic surgery to be performed under sedation. The loading dose of dexmedetomidine was followed by a 15 min infusion of the maintenance dose. The frequency domain heart rate variability parameters from the 5-min Holter electrocardiogram recordings before dexmedetomidine administration were used for the analysis. The statistical analysis also included pre-drug heart rate and blood pressure as well as patient age and sex. The data from 62 patients were analysed. There was no relationship between the decrease in heart rate (42% of cases) and initial HRV parameters, haemodynamic parameters or sex and age of patients. In multivariate analysis, the only risk factor for a decrease in mean arterial pressure (MAP) > 15% from the pre-drug value (39% of cases) was the systolic blood pressure before dexmedetomidine administration as well as for a >15% decrease in MAP sustained at more than one consecutive time point (27% of cases). The initial condition of the ANS did not correlate with the incidence of bradycardia or hypotension; HRV analysis was not helpful in predicting the abovementioned side effects of dexmedetomidine.